Working Memory and Behavioural Problems in Relation to Malay Writing of Primary School Children - Sieak Ling-Teo; Kee Jiar-Yeo (International Journal of Evaluation and Research in Education (IJERE), 2017)
Deficit in working memory is common among young children across multiple abilities. Teachers have pointed to poor memory as one contributing factor to inattentiveness and short attention spans as well as some behavioural problems among students. This study aimed to explore the relationship among working memory, externalizing and internalizing behavioural problems and Malay language (writing). A total of 469 children (aged 8 and 11 year-old) and 17 school teachers were involved in the current study. It was found that working memory, externalizing behavioural problems and internalizing behavioural problems played critical roles in affecting the scores of Malay language (writing) at school. Specifically, there were five predictor variables being found in the regression model namely verbal short-term memory, inattention, somatic complaints, visuospatial working memory and aggression. As a whole, the correlation for the fivefactor model yielded a great result of 0.987.